Expressive language of children with hearing impairment - Elsa Efrina; Mega Iswari; Fauzi Irwanto (Fakultas Ilmu Pendidikan UNP)
Language is an important aspect of communication. The success in communication is determined by the language ability, including the expressive language. Children with hearing impairment have obstacles to conduct expressive language due to the lack of auditory experience. Thus, maternal reflective method can be used to improve the expressive language ability. This method is applied in a structured natural conversation by presenting the language fairly through conversation, visualization, deposit and reflection in order to retrieve the linguistic aspects. The findings showed that the method was effective for improving the ability of expressive language. This research was conducted by the pre-test and post-test values using the Mann Whitney U test, it was obtained that U = 6 and Utab = 2 with n = 5 at a significant level of 95% and α = 0.05. As U was higher than Utab, the alternative hypothesis was accepted.